A Christmas Carol - "Dickens, Charles"; "Lawrence, Michael " (Heinemann Educational: Oxford, 1999)
Literacy World is evolving with the renewed Framework to provide all the support you need to deliver Shared Reading and Writing, Guided Reading, ICT, and Speaking and Listening at Key Stage 2/P4-7. A wealth of quality resources, exceptional teacher support, and complete differentiation make Literacy World your only choice for fiction and nonfiction at Key Stage 2/P4-7.
Keywords: English Fiction-Children's stories